1989
DOI: 10.2307/1962064
|View full text |Cite
|
Sign up to set email alerts
|

Modernization and Participation in the Leninist Developmental Strategy

Abstract: The Soviet Union achieved its stability in the early stages of development not by institutionalizing participation but by forcing departicipation and substituting a functionally distinct form of political activity—involvement in co-production. These policies constitute essential complements in the Leninist developmental strategy. The ability of enlisted involvement to block the growth of participatory pressures tends to decline in later stages of development, however. The result is spontaneous withdrawal from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…Although the authoritarian character of Russian culture is widely accepted, there is evidence of the existence of more liberal, democratic strands in the culture as well (Gibson 1997). Some argue that there have always been important elements of a democratic culture in Russia (Petro 1995), and studies of the late Soviet and immediate post-Soviet periods have revealed both nascent democratic attitudes (Bahry 1987;Hahn 1991) and mounting participatory pressures associated with the country's political changes (Gibson, Duch, and Tedin 1992;Roeder 1989). Over the past decade, the continuation of these pressures, reinforced by the impact of nearly a dozen federal-level elections and referendums, has restructured elite-mass linkages and altered politicians' and voters' perceptions of leader accountability in Russia.…”
Section: Culture Choice and Russian Presidential Approvalmentioning
confidence: 99%
“…Although the authoritarian character of Russian culture is widely accepted, there is evidence of the existence of more liberal, democratic strands in the culture as well (Gibson 1997). Some argue that there have always been important elements of a democratic culture in Russia (Petro 1995), and studies of the late Soviet and immediate post-Soviet periods have revealed both nascent democratic attitudes (Bahry 1987;Hahn 1991) and mounting participatory pressures associated with the country's political changes (Gibson, Duch, and Tedin 1992;Roeder 1989). Over the past decade, the continuation of these pressures, reinforced by the impact of nearly a dozen federal-level elections and referendums, has restructured elite-mass linkages and altered politicians' and voters' perceptions of leader accountability in Russia.…”
Section: Culture Choice and Russian Presidential Approvalmentioning
confidence: 99%
“…Sharlet (1967) contended, for example, that those who participated in public activities organized by the state were no more interested and no more committed to the system than the few who did not and that they were no more efficacious than those who did not. Roeder (1989a) suggested that enforced departicipation might be a more appropriate term to describe citizen involvement. And Shtromas (1984) argued that political action reflected not the internal acceptance of regime norms but merely an external sign of willingness to conform.…”
Section: The Nature Of Soviet Political Participationmentioning
confidence: 99%
“…Cette approche vaudrait également pour la période postcommuniste, puisque la relance de ces dispositifs devait compenser le sous-financement de l'entretien des bâtiments par les finances publiques locales. Sous un autre rapport, on peut les considérer comme le cadre d'exercice d'une citoyenneté spécifique au régime soviétique, visant à impliquer les citoyens dans la coproduction des biens et services publics fournis par l'État 47 . La disparition du Parti communiste de l'Union soviétique -instance d'évaluation de la valeur civique des individus, constituant le centre de cette nébuleuse d'activités bénévoles -a profondément modifié les motifs de l'engagement dans ces structures.…”
Section: Donna : Une Entrepreneuse Dans Un Immeuble Bourgeoisunclassified